Chemical testing of textiles - Fan, Qinguo (Woodhead publishing in textiles., 2005)
Chemical testing of textiles is a new book aimed at giving a full overview of the chemical testing area for both academics and industry. Providing a comprehensive coverage of the chemical analysis procedures for a broad range of textiles. Introductory chapters set out textile chemistry and identification of yarn and fibres, the book then goes on to cover chemical analysis of a range of textile fabrics, chemicals and processes along with chemical assessment of damage and water analysis.